Operability Analysis During Topside Platform Removal with Dynamic Method Due to Wave Load - Murdjito; Muhammad Zakaria Al Amin; Eko Budi Djatmiko; Fajar Rachmadiarto (International Journal of Offshore and Coastal Engineering, 2025)
Topside removal is one of the main activities in the offshore platform decommissioning process, with one of the methods in this process being reverse installation-single lift. Corrosion, one of the common problem factors in steel structures, is used as a parameter to reduce the strength of topside structures. In the structural strength analysis with a thickness reduction of 1.5mm, the maximum unity check values for members and joints are 0.854 and 0.602, respectively. Meanwhile, the dynamic analysis results show that the hoisting line and sling tension increase with increasing wave height and period. The response to increasing tension due to wave loads increases exponentially. The beam seas loading direction produces the highest tension response due to the roll motion response to the crane barge. The shortest hoisting line influences tension due to the higher stiffness value, which results in velocity and acceleration in the topside movement as a pendulum, thereby increasing the snap force. This pattern also applies to the dynamic amplification factor (DAF) and factor of safety (FOS) sling values. The distribution fitting results on the DAF value, 3-Parameter Lognormal, is the correct distribution model with a correlation value 0.999. So, the operational operability in the range of conditions for this research model is 89.4%.